2022
DOI: 10.1108/ejim-04-2022-0180
|View full text |Cite
|
Sign up to set email alerts
|

Modelling organizational resilience structure: insights to assess resilience integrating bounce-back and bounce-forward

Abstract: PurposeThis paper aims to model organizational resilience structure. Based on the central insights of the scientific literature, organizational resilience is modelled as the result of an organizational capacity to bounce-back and bounce-forward.Design/methodology/approachThe paper is based on a quantitative empirical study to support the structural perspective of organizational resilience and investigate the relationships among the dimensions to test the above hypothesis by applying confirmatory factor analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…Furthermore, ensuring representativeness and enhancing external validity, consistent with the study of Bartuseviciene et al . (2023), Strata were formed based on characteristics of firms', i.e.…”
Section: Methodssupporting
confidence: 58%
See 1 more Smart Citation
“…Furthermore, ensuring representativeness and enhancing external validity, consistent with the study of Bartuseviciene et al . (2023), Strata were formed based on characteristics of firms', i.e.…”
Section: Methodssupporting
confidence: 58%
“…Furthermore, ensuring representativeness and enhancing external validity, consistent with the study of Bartuseviciene et al (2023), Strata were formed based on characteristics of firms', i.e. their size divided into two categories, small and medium-sized firms (firm size less than 249) and large firms (firms employ 250 or more people).…”
Section: The Sampling and Data Collectionmentioning
confidence: 99%
“…Knowledge management stands out as a key driver, encompassing the capture, distribution, and efficient utilization of diverse knowledge within GLAM institutions (Von Delft et al, 2019;Li et al, 2022). This aligns with literature emphasizing the role of knowledge in facilitating innovation and organizational resilience (Visvizi et al, 2022;Ciasullo et al, 2022;Troisi et al, 2023;Bartuseviciene et al, 2022;Koskinen, 2005;Antara and Shuvro, 2020;Cerquetti and Cutrini, 2023). The collaborative nature of knowledge management, both internally and externally, highlights the need for skills and expertise in navigating complex collaborative processes.…”
Section: Discussionmentioning
confidence: 58%
“…Leadership and culture have an impact on an organization's capacity for adaptation and support for decision-making, which provides insights and immediately usable solutions to manage crises [56]. Furthermore, leadership and networking denote the organization's ability to endure complex situations during shocks and revert to its pre-crisis state [57]. It can be concluded that, actually, there was a slight difference in the aspects of OR assessment.…”
Section: Discussionmentioning
confidence: 99%